Role of maternal serum homocysteine level on fetal birth weight - Begum, Afrina; Roy, Joya Sree; Sultana, Nilufer; Begum, Noorjahan (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Objective: The present study has been conducted to investigate the role of plasma homocysteine on neonatal birth weight. Methods: This prospective cross sectional analytical study was conducted in the inpatient department of obstetrics & gynecology, Dhaka Medical College Hospital on 120 term, singleton pregnant women. Pregnant women with plasma total bomocysteine >15 µmol/L were termed as having hyperhomocysteinemia (case, n = 25), while women with plasma total homocysteine ?15 µmol/L were considered as notmal (control, n = 95). Neonatal birth weight was the main outcome variable which was compared between case and control groups. Result: The entire women in the case group were in their 3rd decades, while 80% of the control group were in this age range and 10% was below 20 and 10% above 30 years old. The cases were older than the controls (25.6 ± 2.0 vs. 23.7 ± 4.7 years, p = 0.051 ). Over three-quarters (76%) of the cases were SSC level educated, while majority (84.2%) of the controls was primary level educated. Eighty percent of the neonates born of mothers with hyperhomocysteinemia were of low birth weight as opposed to only 9.5% in the control group. The mothers of case-group carry nearly 40(95% of CI= 11.5 - 126.4) times higher risk of having low birth weight babies than the mothers with nonnal homocysteine level. The mean birth weight of neonates of case group was observed to be significantly higher (2.8 ± 0.4 kg) than that of control group (2.2 ± 0.4 kg). Correlation between the two variables shows that as plasma homocysteine level of women increases the birth weight of neonates decreases bearing an inverse relationship between these two variables (r = - 0.326, p < 0.001 ). Conclusion: Pregnant women with elevated plasma total homocysteine carry much higher risk of giving low birth weight babies than the women with normal or low level of total homocysteine. Thus, measuring total homcysteine during pregnancy is of much clinical importance as corrective measure could be taken to avert the adverse pregnancy outcome.